P433 Efficacy of risankizumab by baseline clinical, biochemical, and endoscopic disease severity in moderately to severely active Crohn's disease. (30th January 2023) - Panaccione, R; D'Haens, G; Seenan, J P; Caprioli, F; Siegel, C; Nakamura, M; Wei, S C; Kligys, K; Zhang, Y; Zambrano, J; Song, A P; Ferrante, M
Abstract: Background: Risankizumab (RZB), a p19-anti-interleukin-23 monoclonal antibody, has demonstrated efficacy as induction and maintenance therapy in patients with moderately to severely active Crohn's disease (CD). This post hoc analysis evaluates the efficacy of induction and maintenance RZB therapy by baseline clinical, biochemical, and endoscopic disease severity. Methods: In the ADVANCE (NCT03105128) and MOTIVATE (NCT03104413) studies, patients with moderately to severely active CD and intolerance/inadequate response to ≥ 1 biologic (both studies) and/or conventional therapy (ADVANCE) were randomized to receive intravenous (IV) RZB induction therapy or placebo (PBO) for 12 weeks. Patients achieving stool frequency and/or abdominal pain score clinical response to 12 weeks of induction therapy were rerandomized in the FORTIFY (NCT03105102) study to receive subcutaneous (SC) maintenance RZB (180 mg or 360 mg) or PBO (withdrawal). Clinical and endoscopic endpoints were evaluated by baseline disease characteristics (Crohn's Disease Activity Index [CDAI: ≤ 300, > 300], highsensitivity C-reactive protein [hs-CRP: < 10 mg/L, ≥ 10 mg/L], and Simple Endoscopic Score for Crohn's Disease [SES-CD: 6−15, > 15]). Induction analyses included patients who received RZB 600 mg or PBO; data from the ADVANCE and MOTIVATE studies were pooled. Nonresponder imputation incorporating multiple imputation to handle missing data due to COVID-19 was used. Results: The induction analysis included 527 patients who received RZB 600 mg IV and 362 patients who received PBO. Patients treated with RZB 600 mg IV achieved significantly higher response rates vs PBO at week 12, regardless of subgroup ( P < .05 for all; Figure 1). In the maintenance study, patients treated with SC RZB continued to achieve higher response rates vs the PBO (withdrawal) group at week 52 regardless of subgroup ( P was not < .05 for all; Figure 2). Improvements in clinical and endoscopic outcomes were generally observed from weeks 12 to 52 with RZB treatment across all subgroups. Response rates were generally similar across subgroups in both induction and maintenance studies; endoscopic remission and ulcer-free endoscopy (resolution of ulcer) rates were numerically lower for patients with increased inflammation (hs-CRP > 10 mg/mL) and higher endoscopic activity (SES-CD > 15). Conclusion: RZB induction therapy resulted in higher response rates for clinical and endoscopic outcomes compared with PBO at week 12, regardless of baseline clinical, biochemical, and endoscopic disease severity. RZB also showed durable efficacy with continued RZB maintenance therapy, supporting the long-term use of RZB for patients across a range of baseline disease severity and activity.